Prohibition of Nuclear Weapons: Towards Sustainable Human Security - Intan Innayatun Soeparna (Journal of Human Security, 2023)
Using descriptive and analytical legal research, this study analyses the relationship between the Treaty on the Prohibition of Nuclear Weapons (TPNW) and sustainable human security. It involves critically analysing the rules on the prohibition of nuclear weapons and what has been written and argued regarding human security and sustainable human security. The findings indicate that the TPNW consists of legal obligations for all state parties to abolish nuclear weapons as a prerequisite to permanent human security. It also comprises provisions for achieving sustainable human security. Therefore, the total ban on nuclear weapons is meant to protect human security and sustain it by eliminating the factors of insecurity of human beings due to the threat of using nuclear weapons. <!-- p, li { white-space: pre-wrap; } -->